2012
DOI: 10.1029/2011jd017093
|View full text |Cite
|
Sign up to set email alerts
|

AIRS impact on analysis and forecast of an extreme rainfall event (Indus River Valley, Pakistan, 2010) with a global data assimilation and forecast system

Abstract: [1] A set of data assimilation and forecast experiments is performed with the NASA Global data assimilation and forecast system GEOS-5, to compare the impact of different approaches toward assimilation of Atmospheric Infrared Sounder (AIRS) data. The impact is first assessed globally on a sample of more than forty forecasts per experiment, through the standard 500 hPa anomaly correlation metrics. Next, the focus is on precipitation analysis and precipitation forecast skill relative to one particular event: an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…For example, weather forecast offices utilize EDR via the Advanced Weather Interactive Processing System, and EDR data sets are used for numerous environmental research studies [e.g., Pagano, 2013]. Furthermore, EDR retrievals based upon cloud-cleared radiances (CCRs) [e.g., Susskind et al, 2003;Maddy et al, 2011] have been shown to have a positive impact on forecast models [e.g., Le Marshall et al, 2008;Reale et al, 2008bReale et al, , 2009Reale et al, , 2012aZhou et al, 2010].…”
Section: "Partly Cloudy" (Ir + Mw)mentioning
confidence: 99%
“…For example, weather forecast offices utilize EDR via the Advanced Weather Interactive Processing System, and EDR data sets are used for numerous environmental research studies [e.g., Pagano, 2013]. Furthermore, EDR retrievals based upon cloud-cleared radiances (CCRs) [e.g., Susskind et al, 2003;Maddy et al, 2011] have been shown to have a positive impact on forecast models [e.g., Le Marshall et al, 2008;Reale et al, 2008bReale et al, , 2009Reale et al, , 2012aZhou et al, 2010].…”
Section: "Partly Cloudy" (Ir + Mw)mentioning
confidence: 99%
“…We chose the period to cover the set of catastrophic rain episodes that occurred in late July 2010 along the Indus Valley, in central and northern Pakistan. Reale et al 8 showed that in addition to improving the global forecast skill, the assimilation of quality-controlled AIRS temperature retrievals obtained under partly cloudy conditions produce better precipitation analyses than assimilation of radiances unaffected by clouds.…”
Section: Forecast Impact Experiments Using Quality Controlled Versionmentioning
confidence: 99%
“…We started conducting preliminary experiments at GSFC, assimilating AIRS Version-5 quality controlled temperature profiles into the NCEP operational GDAS system and comparing the results to those using the operational procedure of assimilating AIRS radiances, and also to a Control run which assimilated no AIRS data. These preliminary experiments were conducted starting from July 15, 2010, just as those studied by Reale et al 8 .…”
Section: Forecast Impact Experiments Using Quality Controlled Versionmentioning
confidence: 99%
“…Later, many case studies have attempted to improve the monsoon rainfall in NWP models using various data assimilation methods [e.g., Govindankutty et al, 2008;Rakesh et al, 2009Rakesh et al, , 2010Routray et al, 2010;Singh et al, 2012]. Reale et al [2012] showed improvement in the global forecast skill by assimilating AIRS temperature profiles. They also achieved considerable improvement in analysis as well as forecast of precipitation up to 7 days.…”
Section: Introductionmentioning
confidence: 99%